Analisis Soal Latihan Transformasi Linier Dalam Buku Ajar Aljabar Linier Berdasarkan Teori Prakseologi - Sujatmiko, Ponco; Aryuna, Dyah Ratri; Pramudya, Ikrar; Mardiyana, Mardiyana; Setiawan, Rubono (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2025)
Undergraduate students often struggle to shift froam procedural to conceptual understanding when learning linear transformation. They tend to focus on mechanical procedures while neglecting the underlying concepts. Textbooks play a crucial role in developing conceptual understanding through well-structured and meaningful exercises. Praxeological theory, which maps the relationship among mathematical tasks, techniques, supporting technologies, and underlying theories, provides a comprehensive framework for such analysis. This study aims to analyze linear transformation exercises in Elementary Linear Algebras (11th edition) by Howard Anton and Chris Rorres using a qualitative content analysis based on the praxeological framework. The findings reveal that most exercises have the potential to foster deep conceptual understanding, particularly when learning activities do not stop at the technical stage. Practically, the study offers insights for lecturers and textbook developers in designing exercises that balance procedural demands and conceptual reasoning, thereby enhancing meaningful learning of linear algebra in higher education.